Acute and chronic safety and efficacy of dose dependent creatine nitrate supplementation and exercise performance - Galvan, Elfego (J Int Soc Sports Nutr, 2016)
BACKGROUND: Creatine monohydrate (CrM) and nitrate are popular supplements for improving exercise performance; yet have not been investigated in combination. We performed two studies to determine the safety and exercise performance-characteristics of creatine nitrate (CrN) supplementation. METHODS: Study 1 participants (N = 13) ingested 1.5 g CrN (CrN-Low), 3 g CrN (CrN-High), 5 g CrM or a placebo in a randomized, crossover study (7d washout) to determine supplement safety (hepatorenal and muscle enzymes, heart rate, blood pressure and side effects) measured at time-0 (unsupplemented), 30-min, and then hourly for 5-h post-ingestion. Study 2 participants (N = 48) received the same CrN treatments vs. 3 g CrM in a randomized, double-blind, 28d trial inclusive of a 7-d interim testing period and loading sequence (4 servings/d). Day-7 and d-28 measured Tendo™ bench press performance, Wingate testing and a 6x6-s bicycle ergometer sprint. Data were analyzed using a GLM and results are reported as mean ± SD or mean change ± 95 % CI. RESULTS: In both studies we observed several significant, yet stochastic changes in blood markers that were not indicative of potential harm or consistent for any treatment group. Equally, all treatment groups reported a similar number of minimal side effects. In Study 2, there was a significant increase in plasma nitrates for both CrN groups by d-7, subsequently abating by d-28. Muscle creatine increased significantly by d-7 in the CrM and CrN-High groups, but then decreased by d-28 for CrN-High. By d-28, there were significant increases in bench press lifting volume (kg) for all groups (PLA, 126.6, 95 % CI 26.3, 226.8; CrM, 194.1, 95 % CI 89.0, 299.2; CrN-Low, 118.3, 95 % CI 26.1, 210.5; CrN-High, 267.2, 95 % CI 175.0, 359.4, kg). Only the CrN-High group was significantly greater than PLA (p < 0.05). Similar findings were observed for bench press peak power (PLA, 59.0, 95 % CI 4.5, 113.4; CrM, 68.6, 95 % CI 11.4, 125.8; CrN-Low, 40.9, 95 % CI −9.2, 91.0; CrN-High, 60.9, 95 % CI 10.8, 111.1, W) and average power. CONCLUSIONS: Creatine nitrate delivered at 3 g was well-tolerated, demonstrated similar performance benefits to 3 g CrM, in addition, within the confines of this study, there were no safety concerns.